Statistical Tuning Chart for Mapping Porosity Thickness: a Case Study of Channel Sand Bodies in the Kutei Basin Reservoir - Abdul Haris; Agus Riyanto; Sri Mardiyati (Universitas Ahmad Dahlan, 2018)
Reservoir assessment is not only controlled by the structural framework but also stratigraphical features. Stratigraphical interpretation, which is related to seismic amplitude interpretation, is used to describe petrophysical aspects of channel sand reservoirs such as net porosity and thickness. This paper aims to map the porosity thickness for a case study of channel sand bodies reservoir in the Kutei basin. The study area is complex channel reservoir system that appears to occupy specific area within the depositional system. The geometry of the sediment channel, which thins toward the channel margins, makes this feature similar to be wedge model that could possibly be influenced by tuning effects. The tuning effects introduce pitfall in interpreting high-quality reservoir that is affected by contrasts in acoustic impedance. In order to distinguish high amplitude responses caused by tuning effects and acoustic properties, the analysis of amplitude responses needs to be correlated to the reservoir thickness. The statistical tuning chart is one of the techniques used to correlate amplitude responses and the reservoir thickness. The application of this technique to real data sets shows net porosity thickness map over the targeted reservoir. Thus, high-quality reservoir characterization can be performed to delineate geometric framework of the reservoir.